2021
DOI: 10.1038/s41393-021-00704-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of comorbidities and secondary health conditions among the Finnish population with spinal cord injury

Abstract: Study design A cross-sectional study. Objectives To explore the prevalence of comorbidities, secondary health conditions (SHCs), and multimorbidity in the Finnish population with spinal cord injury (SCI). Setting The data were collected from the Finnish Spinal Cord Injury Study (FinSCI). Participants were identified from three SCI outpatient clinics responsible for the lifelong follow-up of persons with SCI in Finla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
3
8
0
1
Order By: Relevance
“…The high prevalence rates of health conditions secondary to SCI found in the current study are consistent with previous findings from numerous national and single site studies during the last decades (3,6,8,(21)(22)(23)(24)(25)(26)(27). The prevalence rates, however, differed in this inquiry, across both countries and WHO regions.…”
Section: Prevalence Of Self-reported Health Conditionssupporting
confidence: 91%
See 2 more Smart Citations
“…The high prevalence rates of health conditions secondary to SCI found in the current study are consistent with previous findings from numerous national and single site studies during the last decades (3,6,8,(21)(22)(23)(24)(25)(26)(27). The prevalence rates, however, differed in this inquiry, across both countries and WHO regions.…”
Section: Prevalence Of Self-reported Health Conditionssupporting
confidence: 91%
“…The lower odds of comorbidity for those with an incomplete SCI lesion, and for those having a non-traumatic SCI, are in line with previously reported Swiss data (21). The results contrast, however, with findings from a recent Finnish study, in which differences between the groups for SCI severity did not reach statistical significance (27).…”
Section: Impact Of the Health Conditionssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings regarding dyslipidemia have also been reported internationally. Tallqvist et al [ 95 ] surveyed the Finnish population with SCI and observed that 22% had hypercholesterolemia. This value was less than half that of the general population in Finland, where approximately 55% have hypercholesterolemia [ 96 ].…”
Section: Dyslipidemia After Scimentioning
confidence: 99%
“…The authors observed that hypertension was the most common comorbidity, such that 75% of the study participants presented with the condition compared to 26.1% in the general Saudi Arabian population of all ages [ 110 ]. Tallqvist et al [ 95 ] reported that among the Finnish SCI population, hypertension was found in almost 40% of the 884 participants surveyed, which was 3% below that of the general population [ 111 ]. Jörgensen et al [ 75 ], in the Swedish Aging with SCI Study, demonstrated that 33% of the study’s cohort had a previous diagnosis of hypertension, and 55% presented with a hypertensive blood pressure ≥ 140/90 mmHg (27% of the general Swedish population are said to have hypertension [ 112 ]).…”
Section: Hypertension After Scimentioning
confidence: 99%